Cooperative assembly of proteins in the ribosomal GTPase centre demonstrated by their interactions with mutant 23S rRNAs. - Rosendahl, G (1995)
The ribosomal protein L11 binds to the region of 23S rRNA associated with the GTPase-dependent steps of protein synthesis. Nucleotides 1054-1107 within this region of the Escherichia coli 23S rRNA gene were mutagenized with bisulphite. Twenty point mutations (G-->A and C-->T transitions) and numerous multiple mutations were generated. Expression of mutant 23S rRNAs in vivo shows that all the mutations detectably alter the phenotype, with effects ranging from a slight growth rate reduction to lack of viability. Temperature sensitivity is conferred by 1071G-->A and 1092C-->U substitutions. These effects are relieved by point mutations at other sites, indicating functional interconnections within the higher order structure of this 23S rRNA region. Several mutations prevent direct binding of r-protein L11 to 23S rRNA in vitro. These mutations are mainly in a short irregular stem (1087-1102) and within a hairpin loop (1068-1072), where the protein probably makes nucleotide contacts. Some of these mutations also interfere with binding of the r-protein complex L10.(L12)4 to an adjacent site on the rRNA. When added together to rRNA, proteins L10.(L12)4 and L11 bind cooperatively to overcome the effects of mutations at 1091 and 1099. The proteins also stimulate each others binding to rRNA mutated at 1087 or 1092, although in these cases binding remains clearly substoichiometric. Surprisingly, none of the mutations prevents incorporation of L11 into ribosomes in vivo, indicating that other, as yet unidentified, factors are involved in the cooperative assembly process.